Real-World Risk of Gastrointestinal Bleeding for Direct Oral Anticoagulants and Warfarin Users: A Distributed Network Analysis Using a Common Data Model - Cha, Jae Myung; Kim, Myoungsuk; Jo, Hyeong Ho; Seo, Won-Woo; Rhee, Sang Youl; Kim, Ji Hyun; Kim, Gwang Ha; Park, Junseok (Gut and liver, 2024)
Early studies on direct oral anticoagulants (DOACs) reported a higher risk of gastrointestinal bleeding (GIB) compared with warfarin; however, recent studies have reported a reduced risk. Therefore, this study was designed to evaluate the risk of GIB in users of DOAC and warfarin. Using a common data model, we investigated the comparative risk of GIB in subjects from eight hospitals who were newly prescribed DOACs or warfarin. We excluded subjects who had a prior history of GIB or had been prescribed both medications. After propensity score matching, we analyzed 3,347 matched pairs of new DOAC and new warfarin users. The risk of GIB in new DOAC users was comparable to that in new warfarin users (hazard ratio [HR], 0.95; 95% confidence interval [CI], 0.65 to 1.40; p=0.808). New DOAC users had a similar risk of GIB to new warfarin users among older patients >65 years (HR, 1.00; 95% CI, 0.69 to 1.52; p=0.997) and in older patients >75 years (HR, 1.21; 95% CI, 0.68 to 2.10; p=0.509). In addition, the risk of GIB was not significantly different between two groups according to sex. We also found that the risk of GIB in DOAC users was 26% lower in edoxaban or apixaban subgroups compared to rivaroxaban or dabigatran subgroups (HR, 0.74; 95% CI, 0.69 to 1.00; p=0.049). In real-world practice, the risk of GIB in new DOAC users is comparable to that in new warfarin users. In DOAC users, the risk of GIB was lower in edoxaban or apixaban subgroups than rivaroxaban or dabigatran subgroups.